Review of the strategic approach to the problem of poverty in Montenegro - Janković, Uglješa (Ревија за социјална политика/Journal of Social Policy, 2015)
Strategic approaches to the problem of poverty were identified asthe objective solutions in other countries and the third world. The firststrategy for the reduction of poverty in Montenegro was implemented in2003. A few years later (2007), the Government of Montenegro creatednew strategy in which the concept of social inclusion was incorporated.Along with the implementation of the above strategic approaches werealso carried out the reform of the education and social welfare, with theclear objective of facilitation the social inclusion of marginalized groups.The main subject of this study is the application of the method of timeseries analysis in determining the degree of efficiency of applied strategicapproach. If the strategy adopted in 2003and 2007produced results, thenwe can identify them as the key points where there is a change in trend ofindicators that we use to predict the level of poverty. We will use the twoavailable measures and test key hypotheses, unemployment and number ofusers of social help support.